2022
DOI: 10.3390/ijms232314918
|View full text |Cite
|
Sign up to set email alerts
|

IL-1RAP, a Key Therapeutic Target in Cancer

Abstract: Cancer is a major cause of death worldwide and especially in high- and upper-middle-income countries. Despite recent progress in cancer therapies, such as chimeric antigen receptor T (CAR-T) cells or antibody-drug conjugate (ADC), new targets expressed by the tumor cells need to be identified in order to selectively drive these innovative therapies to tumors. In this context, IL-1RAP recently showed great potential to become one of these new targets for cancer therapy. IL-1RAP is highly involved in the inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 157 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…Studies have revealed that peptidoglycan, lipoprotein, mycoplasma lipopeptides, flagellin, CpG DNA and double-stranded RNA specifically bind and activate TLRs, thereby inducing IκBζ production ( 49 , 50 ). IL-1 superfamily members are often classified into four subfamilies based on the coreceptors that they bind: the IL-1, IL-33, and IL-36 subfamilies, whose members function in conjunction with the coreceptor IL-1RAP, and the IL-18 subfamily, which members bind a different coreceptor ( 51 ). In IL-1β-treated primary chondrocytes, NFKBIZ is one of the most significantly upregulated genes ( 39 ).…”
Section: Iκbζ Is Induced Via Inflammatory Signal P...mentioning
confidence: 99%
“…Studies have revealed that peptidoglycan, lipoprotein, mycoplasma lipopeptides, flagellin, CpG DNA and double-stranded RNA specifically bind and activate TLRs, thereby inducing IκBζ production ( 49 , 50 ). IL-1 superfamily members are often classified into four subfamilies based on the coreceptors that they bind: the IL-1, IL-33, and IL-36 subfamilies, whose members function in conjunction with the coreceptor IL-1RAP, and the IL-18 subfamily, which members bind a different coreceptor ( 51 ). In IL-1β-treated primary chondrocytes, NFKBIZ is one of the most significantly upregulated genes ( 39 ).…”
Section: Iκbζ Is Induced Via Inflammatory Signal P...mentioning
confidence: 99%
“…IL1RAP is a crucial co-receptor expressed in numerous tissues and cell types, emphasizing its pivotal role in immune responses, cancers, and infectious diseases (38). The IL1RAP serves as a subunit to the type I IL-1 receptor (IL-1RI), a specific plasma membrane receptor, which facilitates the transmission of numerous biological effects of the pro-inflammatory cytokine IL-1 on an array of target cells (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, CD19 ( 211 , 212 ), CD26 ( 213 ), CD38 ( 214 ), and IL-1-Receptor-associated Protein (IL-1-RAP) ( 215 ) have been investigated as potential target antigens for a CAR-T-cell therapy approach in CML. IL-1-RAP is of pronounced interest as its expression correlates with the formation of the Philadelphia chromosome in CML cells ( 216 ) and is often expressed in increased levels on malignant hematopoietic cells ( 217 ). CAR-T cells targeting IL-1-RAP can be produced semi-automatically and GMP-compliant since 2023 ( 218 ).…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%